DESIGN THINKING APPROACH FOR SUSTAINABILITY OF FREE MEAL PROGRAM AT AL-QUDS TRADITIONAL ISLAMIC BOARDING SCHOOL - Zanesty, R. Aditya Rayhan; Adhyaksa, Rangga Pijar; Mahdi, Muhammad Haikal (LPPM Universitas Malikussaleh, 2024)
The free meal initiative in Indonesia aims to combat malnutrition and stunting. Introduction: This study explores the implementation of the free meal program at Pondok Pesantren Al-Quds. Purpose of the Study: To identify challenges and propose solutions for sustainable meal management. Objective of the Paper: To analyze financial, logistical, and nutritional issues while developing targeted interventions. Research Methodology: Utilizing the Design Thinking approach, qualitative data were gathered through interviews and surveys with 27 participants from the boarding school community. General Findings: Key challenges included financial instability, inconsistent meal quality, and the need for standardized meal management systems. Proposed solutions, such as an Excel-based budgeting tool and financial literacy training, aim to enhance the programs sustainability and effectiveness. The findings highlight the importance of structured management practices and community involvement in successfully implementing the free meal initiative.